2019
DOI: 10.3390/plants8060152
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of P700 Induces Alternative Electron Flow in Photosystem I in Wheat Leaves

Abstract: Oxygen (O2)-evolving photosynthetic organisms oxidize the reaction center chlorophyll, P700, in photosystem I (PSI) to suppress the production of reactive oxygen species. The oxidation of P700 is accompanied by alternative electron flow in PSI (AEF-I), which is not required for photosynthetic linear electron flow (LEF). To characterize AEF-I, we compared the redox reactions of P700 and ferredoxin (Fd) during the induction of carbon dioxide (CO2) assimilation in wheat leaves, using dark-interval relaxation kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 47 publications
5
29
1
Order By: Relevance
“…Under the two pO 2 conditions, vH + showed a positive linear relationship with Jf, with an origin of zero. These results agree with those of Avenson et al [26] Kadota et al [38] reported that the electron flux in ferredoxin (Fd)-dependent cyclic electron flow (CEF) activity is negligible compared to the electron flux in LEF under high light intensity conditions [38]. Therefore, it is implied that in a steady state, vH + is equal to the rate of H + accumulation in the thylakoid lumen driven by LEF.…”
Section: Electron Flux Of Photosynthetic Lef Matches the Rate Of Ecs supporting
confidence: 89%
See 1 more Smart Citation
“…Under the two pO 2 conditions, vH + showed a positive linear relationship with Jf, with an origin of zero. These results agree with those of Avenson et al [26] Kadota et al [38] reported that the electron flux in ferredoxin (Fd)-dependent cyclic electron flow (CEF) activity is negligible compared to the electron flux in LEF under high light intensity conditions [38]. Therefore, it is implied that in a steady state, vH + is equal to the rate of H + accumulation in the thylakoid lumen driven by LEF.…”
Section: Electron Flux Of Photosynthetic Lef Matches the Rate Of Ecs supporting
confidence: 89%
“…Furthermore, we recently found that the LEF rate and Fd oxidation rate have a similar relationship to that between the LEF rate and Jg [38]. These results show that ferredoxin (Fd)-dependent CEF [40][41][42][43][44][45][46] is negligibly small; that is, photosynthetic LEF is responsible for the majority of ∆pH formation [38]. The induction mechanism of ∆pH formation across the thylakoid membranes is shown in the following manner: ∆pH formation is observed as an ECS signal increase [26,47].…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, a decrease in Jg does not induce the reduction of Fd [61]. For example, lowering the intercellular partial pressure of CO 2 decreases the photosynthesis rate, and Jg decreases; however, the reduced level of Fd either does not change or decrease.…”
Section: Robust Relationships Support Tight Coupling Between the Lighmentioning
confidence: 95%
“…These results indicate that photosynthetic linear electron flow is the sole driver of both photosynthesis and photorespiration. In other words, Jf = Jg 1Recently, a positive linear relationship with an origin of zero between the reduced Fd oxidation rate (vFd) and the photosynthetic linear electron flow rate (J f ) was found (Equation 2 [61]). These results indicate that electron flow via Fd is driven by both photosynthesis and photorespiration.…”
Section: Robust Relationships Support Tight Coupling Between the Lighmentioning
confidence: 99%
See 1 more Smart Citation